Cia de Dança Palácio das Artes de Belo Horizonte: movimentos de uma experiência artístico-profissional continuada (1971-2013) - Tania Mara Silva Meireles (2016)
The theme of this thesis is the Belo Horizontes theatrical dance, selecting as object of study the Cia de Dança Palacio das Artes CDPA (Arts Palace Dance Company). The CDPA is understood as a centralized locus of a series of actions, experiences and creations determinants in building a professional dance profile, grounded by the set of aesthetic, technical and reflective procedures. The diachronic period covered 1971-2013 relates to the foundation year of the official dance company of Minas Gerais state and the year of the beginning of this research. Therefore, the research has focused on two analytical sources: the CDPAs acquis filed in the Center of Acquaintanceship Information and Memory João Etienne Filho based at Clovis Salgado Foundation, in particular the Cia dance Programs; and the Interviews with the artists involved in this process. The working theory is founded by national and international authors, including: Alvarenga (2002. 2009) for his thorough investigation concerning the establishment and the memory of the dance of Minas Gerais state; Rodrigues (2003. 2010), creator of the Dancer-Researcher-Performer method [DRP] methodology in which the focus is on the identity of the body, meeting place of experiences and memories incorporated in the work of the CDPA work process; Walter Benjamin (1987. 2012) for its conceptual understanding of experience articulated to narrative and memory ideas, and for whom the experience becomes knowledge by accumulation, extension and consequences of this experience; and Larrosa (2012. 2014), in dialogue with Benjamin in his contemporary understanding of experience as a valid and legitimate form of knowledge. It is considered that the process of the artistic career of CDPA was embodied by the set of shared experiences uninterruptedly along its 42 years of existence. This process becomes crucial to be understood in this paper as a continuing professional experience.